O sistema educacional no Brasil do século XX: um percurso historiográfico - Paula, Sebastiana Candida Gomes de (2008)
This assignment s scope is Linguistic Historiography, aiming at an investigation on the basic education teachers, especially in the emphasis of teaching the Portuguese Language. The focus of the hereby developed assignment presumes that the education, as an cultural phenomena, fits itself in a social, economic and political context, and, therefore, the analysis was made within the fields of History and Linguistic Historiography, both of which allow an observation of the interactions between the political, social and educative dimensions. Grounded on these motives, some documents (Laws, Rules and Standards, Curricular Organization), which are part of the base of the educational reforms, occurred within the studied period, will be analyzed.